2009
DOI: 10.1007/s11136-009-9548-1
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of overall quality of life in women over the first year after surgery for early stage breast cancer

Abstract: QOL domains and facets contributed differently to overall QOL at various time points across treatment in women with early stage breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…The second important result of our study was that three of the 12 variables evaluated were associated to a better sexual QoL: (i) low score on negative feelings; (ii) being on hormonal treatment; and (iii) having a partner. In agreement with our findings, negative feelings or depression have been associated with worse general QoL in gender‐dysphoric adults [36] and in medical conditions [38]. Hormonal treatment as a factor associated to a better sexual QoL is in line with the results of Gorin‐Lazard et al.…”
Section: Discussionsupporting
confidence: 93%
“…The second important result of our study was that three of the 12 variables evaluated were associated to a better sexual QoL: (i) low score on negative feelings; (ii) being on hormonal treatment; and (iii) having a partner. In agreement with our findings, negative feelings or depression have been associated with worse general QoL in gender‐dysphoric adults [36] and in medical conditions [38]. Hormonal treatment as a factor associated to a better sexual QoL is in line with the results of Gorin‐Lazard et al.…”
Section: Discussionsupporting
confidence: 93%
“…The authors found that emotional distress decreased with time since treatment . Finally, the subjective perception that quality of life depends on the use of medications predicted better quality of life …”
Section: Resultsmentioning
confidence: 95%
“…Sleep difficulties predicted more psychological distress and poorer quality of life, but 3 studies found no significant associations . Reports of more pain predicted more depressive and anxiety symptoms .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations